Pendampingan Ibu Rumah Tangga Dalam Perencanaan Dana Kesehatan Berbasis Komunitas - Nana Erika; Supriati; Indri Safrina (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
The community-based mentoring program for housewives in health fund planning aims to improve family financial management skills and promote sustainable financial independence. Many families, especially those from lower-income communities, lack awareness and preparedness in allocating funds for health needs. This often leads to financial difficulties when urgent medical expenses arise. Through a community-based approach, this program provides training, group discussions, and practical simulations for housewives on how to manage and plan health funds effectively. The results show a significant improvement in participants’ knowledge, attitudes, and skills in family financial management related to health. Additionally, the establishment of community savings groups has fostered solidarity and mutual financial support among members. This program demonstrates that empowering housewives through community participation can strengthen household economic resilience and encourage greater community self-reliance in managing health funds.